2015
DOI: 10.1038/ncomms10154
|View full text |Cite
|
Sign up to set email alerts
|

Abasic pivot substitution harnesses target specificity of RNA interference

Abstract: Gene silencing via RNA interference inadvertently represses hundreds of off-target transcripts. Because small interfering RNAs (siRNAs) can function as microRNAs, avoiding miRNA-like off-target repression is a major challenge. Functional miRNA–target interactions are known to pre-require transitional nucleation, base pairs from position 2 to the pivot (position 6). Here, by substituting nucleotide in pivot with abasic spacers, which prevent base pairing and alleviate steric hindrance, we eliminate miRNA-like o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 50 publications
0
44
0
Order By: Relevance
“…It has only been reported as a target gene of two miRNA (miR-27a and miR-124) [22, 23]. However, relationship between miR-224 and PCSK9 is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has only been reported as a target gene of two miRNA (miR-27a and miR-124) [22, 23]. However, relationship between miR-224 and PCSK9 is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…4 Thus, the development of modifications that avoid miRNA-like off-targeting is an active area of research. 57 Importantly, recent advances in structural studies of key protein–RNA complexes of the RNAi pathway have enabled structure-guided optimization of siRNA properties. 8,9 …”
mentioning
confidence: 99%
“…11,12,19 Indeed, a recent report showed that introduction of an abasic residue at position 6 of the guide strand reduced miRNA-like off-target effects. 20 However, T M studies with model RNA duplexes indicated that 7-EAA triazole NEtPip does not substantially destabilize the duplex structure (ΔT M = 1.5 °C replacing one A-U pair with one 7-EAA triazole NEtPip-U base pair in a 12 bp duplex where a mismatch destabilizes this duplex ΔT M = 8.5 °C) and a crystal structure of a 7-EAA triazole NEtPip-containing RNA duplex showed typical A-form geometry. 15 Thus the influence of 7-EAA triazole NEtPip on miRNA-like off targeting appears to arise from effects not previously observed with sugar modified guide strands.…”
Section: Resultsmentioning
confidence: 99%